Fatah, Arafat Abdul-Hamid. “The Methodology of the Mutakallimūn (Theologians): An Analytical Study,” Year 2, Issue 8 (Spring 1416 AH/ 1997 CE), Pp. 85-108. - فتاح, عرفان عبدالحميد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1997)
Arafat Abdul-Hamid Fatah’s study examines the methodologies and approaches developed by scholars of ʿaqīdah (doctrinal belief) and kalām (theology) to expose the historical considerations and the cultural and societal details that became associated with both, highlighting what is useful in developing methodologies of thought among Muslims in the face of emerging challenges and problems. His study explains the foundations put forth by the mutakallimūn (theologians) to substantiate the validity of Islamic ʿaqīdah and defend it, including the methodological study of human knowledge, critical reading of the foundations of religion, their position towards the denial of naskh (abrogation) of Divine laws, repelling the ambiguity associated with the notions of tashbīh (anthropomorphism) and mumāthalah (similitude or correspondence; i.e., between God and creation), and the transcendence of Prophets from their sins. His article also presents the points of difference between the Islamic conception and Greek philosophy regarding aspects of the Divine, and it concludes with critical and methodological observations of the Salafi current.